TEOLOGI ISTIRAHAT DAN HUSTLE CULTURE: TEOLOGI ISTIRAHAT DALAM KELUARAN 23:12 DAN IMPLIKASINYA TERHADAP FENOMENA HUSTLE CULTURE - Saputra, Jefri Andri (SEKOLAH TINGGI TEOLOGI DAN ENTREPRENEURSHIP PRINGGADING (STEP) SEMARANG, 2024)
This article aims to respond to the hustle culture phenomenon in church life and today's society. People recognize hustle culture as an alternative to success. However, hustle culture constructs a way of working that works all the time and results in chronic fatigue, depression, and even death. The author responds to this problem by studying the text of Exodus 23:12 using the historical-grammatical interpretation method. The author finds that hustle culture is the new face of slavery in the modern era. The author offers to deconstruct the hustle culture version of the concept of success through a holistic perspective. Successful work also requires balanced attention to employee achievement and welfare. Workers and companies must limit working time to comply with the employment contract without additional work. Workers should not fight fatigue but should take time to rest and calm down. Some of these alternatives are the author's offer to address the impact of hustle culture.